Oncology practice during COVID-19 pandemic: a fast response is the best response - Cinthya Sternberg (Revista da Associação Médica Brasileira)
SUMMARY The first confirmed case of coronavirus disease 2019 (COVID-19) in Brasil was reported on February 25th, 2020, and by April 3rd, 8076 were confirmed in the country. As COVID-19 disease incidence escalates in Brasil, management of cancer patients requires immediate action and oncology clinics are urged to establish a contingency plan. We have installed a COVID-19 Management Committee to elaborate and implement best practices to assist cancer outpatients as well as to provide a safe environment for clinical staff and other employees at the outpatient clinics. The challenges of cancer treatment in the midst of COVID-19 global pandemic highlight the importance of a rapid response by institutions, where organizational structure, strategic planning, agility in guidelines implementation and alternative ways to protect and support clinical staff, employees and patients may be the key to mitigate pandemic effects.